2011
DOI: 10.4166/kjg.2011.58.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Procalcitonin with Ranson, APACHE-II, Glasgow and Balthazar CT Severity Index Scores in Predicting Severity of Acute Pancreatitis

Abstract: Serum PCT was a promising simple biomarker and had similar accuracy of APACHE-II scores as predicting severity of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
4
37
0
3
Order By: Relevance
“…A CRP level above 150 mg/L at 48 hours has a sensitivity and specificity of 80% and 76%, respectively, for predicting severe AP (15). A CRP cutoff level of 82 mg/L was studied in a Korean study, and the sensitivity, specificity and accuracy of CRP were reported to be 68.4%, 68%, and 68.2%, respectively (25). In our study, 150 mg/L was used as a CRP cutoff value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CRP level above 150 mg/L at 48 hours has a sensitivity and specificity of 80% and 76%, respectively, for predicting severe AP (15). A CRP cutoff level of 82 mg/L was studied in a Korean study, and the sensitivity, specificity and accuracy of CRP were reported to be 68.4%, 68%, and 68.2%, respectively (25). In our study, 150 mg/L was used as a CRP cutoff value.…”
Section: Discussionmentioning
confidence: 99%
“…The scarce availability of this test in laboratories is the main problem associated with this method (25,26). Another important acute phase reactant is CRP, and it has been studied in the literature for this aim.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no specific biochemical parameter available to be used in the diagnosis and severity assessment of acute pancreatitis (14). Three hormones encoded by the ghrelin gene have been discovered in recent years, namely obestatin, de-acylated ghrelin, and acylated ghrelin, also known as bioactive peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These systems may be stated as Ban's, Agarwal-Pitchumoni, Ranson, Glasgow (Imrie), and the acute physiology and chronic health evaluation (APACHE-II). However, these scoring systems are rather complex and difficult for use in clinical practice (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 21 patients (13%) were classified as severe AP, and two (10%) of these patients died during hospitalization. Some studies have reported that the cause of AP was not related to disease severity [15][16][17] . However, in this study, among the etiologies of AP, alcohol showed a significant association with patients with severe AP (P = 0.030).…”
Section: Discussionmentioning
confidence: 99%